How young companies can effectively manage their slack resources over time to ensure sales growth: the contingent role of value-based selling - Ad de Jong; Nicolas A. Zacharias; Edwin J. Nijssen (Journal of the Academy of Marketing Science, 2020)
This research aims to bridge the entrepreneurship and marketing/sales literature streams by studying how young firms enable their resource endowments using value-based selling. Drawing on effectuation logic, the authors examine how young firms can achieve sales growth by using human and financial resource slack during the early years of their existence and accounting for the impact of the variability of these resources over time. The integrated framework and hypotheses are tested using unique, multisource (survey and objective archival) longitudinal panel data from 71 young firms covering a seven-year period. As anticipated, the findings show that both financial and human resource slack are negatively related to young firms' sales growth over time and that financial resource slack variability exerts a positive impact and human resource slack variability exerts a (nonsignificant) negative impact. The results also confirm the importance of value-based selling as a guiding mechanism that significantly alters the effects of both types of resource slack and their variability over time. While value-based selling can help a young firm use slack to grow more effectively, it also has a dark side in that it can stand in the way of risk taking.
Keywords: 330; Resource slack; Value-based selling; Entrepreneurship; Longitudinal panel data